Sensitivity to Anilinopyrimidines and Phenylpyrroles in «Botrytis cinerea» in North-Italian Vineyards - Garibaldi, Angelo; Bertetti, Domenico; Gullino, M. Lodovica; Monchiero, Matteo (Phytopathologia Mediterranea, 2000)
Several commercial vineyards, located in Piedmont (Northern Italy), were monitored in order to evaluatethe sensitivity of Botrytis cinerea Pers., the causal agent of grey mould, to five classes of botryticides: benzimidazoles,dicarboximides, phenylcarbamates, anilinopyrimidines and phenylpyrroles. Strains of B. cinerea resistant toanilinopyrimidines were easily detected, particularly in 1999, a year characterized by high disease pressure, even invineyards not sprayed with that class of fungicides. Fludioxonil-resistance, on the contrary, was not detected. Resistanceto benzimidazoles and dicarboximides was at previous observed levels. For the first time, resistance tophenylcarbamates was detected in the field. Strains of B. cinerea showing multiple resistance to benzimidazoles,dicarboximides and anilinopyrimidines and maintaining a good level of virulence, as shown by tests carried out onwounded apples, are present in Italian vineyards. Strategies in the use of the botryticides are discussed, in order toavoid a loss of disease control.